Наближення температурної залежності в’язкості поширених газів для умов лабораторних приміщень - Теплюх, З.; Ділай, І. (Видавництво Національного університету “Львівська політехніка”, 2005)
In the article the known data of temperature dependence for viscosity of prevalent gases in range 0…60 0C are analysed and approcsimation coefficients of this dependences are presented.
Keywords: 533.2.7